Exploring the Interdisciplinary Roles of Dermatologists and Psychiatrists in the Management of Excoriation (Skin-picking) Disorder - Danielle Mintsoulis (University of Ottawa Journal of Medicine, 2015)
ABSTRACT: Excoriation disorder is a mental health disorder characterized by excessive picking of one’s skin resulting in clinically significant functional impairment. Diagnosing this condition has been historically challenging due to the varied associated behaviours and lack of inclusion in the Diagnostic and Statistical Manual of Mental Disorders (DSM). As dermatologists and psychiatrists are the specialists most likely to encounter these individuals, this article discusses the new DSM-5 criteria and outlines the approaches and treatment options for these specialists to optimally manage patients with excoriation disorder.